MicroRNA‐766 promotes cancer progression by targeting NR3C2 in hepatocellular carcinoma. Issue 1 (21st August 2018) - Yang, Chao; Ma, Xiang; Guan, Ge; Liu, Huan; Yang, Yuling; Niu, Qinghui; Wu, Zehua; Jiang, Yueping; Bian, Cheng; Zang, Yunjin; Zhuang, Likun
ABSTRACT: MicroRNAs (miRNAs) have been reported to play important roles in tumor progression of various cancers. However, the clinical significance and biologic function of miR‐766 in hepatocellular carcinoma (HCC) remain unknown. In this study, we investigated the roles of miR‐766 in HCC progression using HCC cell lines and a xenograft mouse model. miR‐766 expression in tumor tissues and adjacent nontumorous liver tissues of patients with HCC was evaluated by quantitative RT‐PCR. Our results showed that miR‐766 promoted proliferation and metastasis of HCC cells in vitro and in vivo and that NR3C2 was a direct target of miR‐766 and involved in miR‐766–mediated proliferation and metastasis of HCC cells. We also found that miR‐766 affected the β‐catenin signaling pathway by targeting NR3C2. Furthermore, miR‐766 was significantly up‐regulated in HCC tissues and was correlated with the prognosis of patients with liver cancer. Taken together, our results show that miR‐766 affects HCC progression by modulating NR3C2 expression and is a possible new therapeutic target for patients with HCC.—Yang, C., Ma, X., Guan, G., Liu, H., Yang, Y., Niu, Q., Wu, Z., Jiang, Y., Bian, C., Zang, Y., Zhuang, L. MicroRNA‐766 promotes cancer progression by targeting NR3C2 in hepatocellular carcinoma. FASEB J. 33, 1456–1467 (2019). www.fasebj.org